2020
DOI: 10.1001/jamaneurol.2019.3238
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neurofilament Light Chain Levels in Patients With Presymptomatic Multiple Sclerosis

Abstract: IMPORTANCE Unrecognized demyelinating events often precede the clinical onset of multiple sclerosis (MS). Identification of these events at the time of occurrence would have implications for early diagnosis and the search of causal factors for the disease.OBJECTIVE To assess whether serum neurofilament light chain (sNfL) levels are elevated before the clinical MS onset. DESIGN, SETTING, AND PARTICIPANTSNested case-control study among US military personnel who have serum samples stored in the US Department of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
135
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 181 publications
(147 citation statements)
references
References 35 publications
5
135
0
Order By: Relevance
“…11 The high sensitivity of the SIMOA â technology provided the reliable quantification of blood NfL in MS. 11 On the group level, blood NfL in MS was higher than in healthy controls 32,44,62,66 with progressive MS having higher levels of blood NfL than relapsing MS. 16,32 The increased levels of blood NfL in progressive versus relapsing MS was unexpected and contrasted with lower levels of NfL in the CSF in progressive versus relapsing MS. 67 This remains unexplained but could be related to a breakdown of the BBB in progressive MS linked to aging and/or a contribution from the peripheral nervous system. Ascherio's group reported that in a military cohort, blood NfL was able to identify neuronal damage 6 years prior to the clinical disease onset, 68 thus neurodegeneration was already present at the prodromal stage of MS. A number of studies have found that disease activity as measured by clinical or MRI assessment is associated with an increase in blood NfL levels in both adult 16,32,66,[69][70][71][72][73] and pediatric patients. 74,75 Of note, the association of blood NfL with disability was less in progressive MS, which may be related to the older age of this population that also have comorbidities.…”
Section: Blood Nfl In Neurological Diseasesmentioning
confidence: 99%
“…11 The high sensitivity of the SIMOA â technology provided the reliable quantification of blood NfL in MS. 11 On the group level, blood NfL in MS was higher than in healthy controls 32,44,62,66 with progressive MS having higher levels of blood NfL than relapsing MS. 16,32 The increased levels of blood NfL in progressive versus relapsing MS was unexpected and contrasted with lower levels of NfL in the CSF in progressive versus relapsing MS. 67 This remains unexplained but could be related to a breakdown of the BBB in progressive MS linked to aging and/or a contribution from the peripheral nervous system. Ascherio's group reported that in a military cohort, blood NfL was able to identify neuronal damage 6 years prior to the clinical disease onset, 68 thus neurodegeneration was already present at the prodromal stage of MS. A number of studies have found that disease activity as measured by clinical or MRI assessment is associated with an increase in blood NfL levels in both adult 16,32,66,[69][70][71][72][73] and pediatric patients. 74,75 Of note, the association of blood NfL with disability was less in progressive MS, which may be related to the older age of this population that also have comorbidities.…”
Section: Blood Nfl In Neurological Diseasesmentioning
confidence: 99%
“…10 In MS, elevated levels of serum neurofilament light have been shown to correlate with disease activity 11 and worse long-term clinical and paraclinical outcomes. 7,[11][12][13][14][15][16][17][18][19][20][21] Although these studies demonstrate utility for serum neurofilament light level as a potential biomarker associated with disease activity and shorter-term prognosis, information is scarce on the association of serum neurofilament light level at first MS presentation with long-term disease outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, higher NfL levels at baseline were associated with a more rapid decrease in brain volume and predicted higher number of enhancing lesions, confirming the role of NfL as a potential marker of neuronal and axonal damage in CIS and early MS. Finally, in a case-control study performed among US military that analyzed serum samples of 60 subjects asymptomatic at time of sampling who then developed MS (6 years later as a median), the authors observed increased serum NfL levels in cases that would develop MS in comparison to healthy controls, demonstrating a potentially useful value of serum NfL in predicting future development of/ evolution to MS [31] .…”
Section: Nfl In Subjects With Clinically Isolated Syndrome and Radiolmentioning
confidence: 97%